Evidence for a latent viruslike agent in cassava - Gabriel, C.J.; Walsh, R.; Nolt, Barry L. (1987)
Several species of double-stranded RNA (dsRNA) were found to occur in the cassava clone Secundina, which was thought to be virus- free. A large dsRNA molecule (6.6 x 106 Mr = relative molecular mass)(L-dsRNA) was shown to be graft, but not mechanically transmitted and occurred primarily in a nuclear-rich fraction isolated from dsRNA-containing Secundina plants. Viruslike particles were not detected in plants containing the L-dsRNA using a var. of purification procedures. L-dsRNA was also found in 2 non- Secundina cassava introductions. Smaller dsRNAs(S-dsRNAs), ranging mainly between 0.61-0.41 x 106 Mr, were also detected in some Secundina plants containing the L-dsRNA. The S-dsRNAs were not transmissible by mechanical inoculation or grafting. All dsRNAs could be eliminated by meristem-tip culture of infected plants. DsRNA analysis is recommended for indexing cassava for this latent viruslike agent. (AS)